Study on algae source pollution and ecological risk control in urban inner lakes - GAO Tingting; CAI Chuanzun; CHEN Yangyang; LIU Chengguo; AO Dong (Xi'an Gongcheng Daxue xuebao)
Aiming at the problem of frequently occurred eutrophication in urban inner lakes and the serious harm to their ecological security, we took Hancheng Lake in Xi'an as the research object, used hydrodynamic and eutrophication models, and scenario simulation analysis of boundary conditions to analyze the causes of water quality deterioration and proposed water quality improvement plans. The results indicate that the model has a good fit with a coefficient higher than 0.8 after parameter calibration, and can effectively simulate the evolution of the water quality. The scenario simulations reveal that algal growth is influenced by both external environmental factors and nutrient substances, with nutrient substances (particularly inorganic phosphorus) having a greater impact. The most effective measures for water quality improvement include purifying water quality in source water, and increasing the amount of water replenishment, macrophyte cultivation and the capture of algae by zooplankton. Given the actual situation, a combination of adjusting the amount of water replenishment, adopting eco-purification measures through water diversion channels, and implementing biological manipulation can guarantee the water quality of Hancheng Lake. Moreover, when the water replenishment is insufficient, the optimal hydraulic residence time should be controlled at 35 days.